Identification of Begomoviruses Causing Yellow Curl Disease in Chilli in West Java - Wiridannisaa, Nurul; Kasim, Niken Nur; Prihatin, Prihatin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Begomoviruses are among the most destructive plant viruses infecting chili (Capsicum annuum L.), leading to significant yield losses in tropical and subtropical regions. In Indonesia, particularly in West Java, the incidence of viral diseases in chili plants has increased, yet molecular identification of the causal agents remains limited. This study aimed to detect and characterize Begomovirus infections in chili plants from Cianjur and Bogor using molecular techniques. Symptomatic leaf samples showing chlorosis, curling, and stunted growth were collected and analyzed using Polymerase Chain Reaction (PCR) with universal Begomovirus primers (SPG1/SPG2). Amplicons were sequenced and compared using BLAST analysis to determine nucleotide identity and phylogenetic relationships. Results showed that all tested samples were positively infected with Begomovirus, with sequence homologies ranging from 87% to 96% with Pepper yellow leaf curl Indonesia virus (PYLCIV). Phylogenetic analysis revealed that isolates from Cianjur and Bogor clustered differently, indicating genetic variability possibly influenced by agroecological conditions and seed exchange practices. Findings highlight the presence of multiple Begomovirus species infecting chili in West Java and underscore the importance of early molecular detection in managing viral diseases. It is recommended that integrated disease management strategies be developed, including the use of virus-free seedlings, resistant cultivars, and region-specific monitoring systems.